Pengaruh Time Budget Pressure, Locus of Control, Task Complexity, dan Turnover Intention pada Dysfunctional Audit Behavior - Hana Arsantini, Margaretta; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi, 2018)
This study aims to determine the effect of time budget pressure, locus of control, task complexity, and turnover intention on dysfunctional audit behavior. Sampling in this study was conducted in non-probability sampling, namely by using a purposive sampling approach that is as much as 78 samples. The method of data collection for this study is to use survey methods with questionnaires. The analysis technique used in this study uses multiple linear regression used to determine the influence of independent variables on the dependent variable. Based on the results of the analysis and discussion of the results of the research budget budget pressure, task complexity, and turnover intention have a positive influence on dysfunctional audit behavior. Whereas, locus of control has a negative influence on dysfunctional audit behavior. Keywords : time budget pressure, locus of control, task complexity, turnover intention, dysfunctional audit behavior.